"You try to keep a brave face on but inside you are in bits": Grandparent experiences of engaging with professionals in Children's Services. (May 2017) - Tarrant, Anna; Featherstone, Brid; O'Dell, Lindsay; Fraser, Clare
This article presents findings from an evaluation conducted in 2012, of the advice and advocacy service provided by the charity Family Rights Group for families involved with children's services. It specifically focuses on the experiences of grandparents and explores accounts from grandparents who were either in the process of seeking care of their grandchildren or were already caring for grandchildren but without formal support or recognition. The findings suggest that there is a need to pay greater attention to the fears of such grandparents about children's services in a context where there appears to be a policy preference for adoption. Also evident is a paradox at the heart of contemporary social work practices towards grandparents. While some felt dismissed and marginalized very quickly by social workers and imaginative approaches to care possibilities did not appear to be pursued, others were carrying enormous burdens of care often for very long periods of time without either financial support or legal recognition. To strengthen the care options for children and respect the ethic of care that is clearly to be observed operating in grandparenting practices, it is suggested that a more thorough interrogation of the multiple and often highly contradictory meanings attached to family is required on the part of social workers.